2020
DOI: 10.3389/fcvm.2020.592201
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Pharmacology and GEO Database Mining Revealed the Therapeutic Mechanism of Xuefu Zhuyu Decoration for Atherosclerosis Cardiovascular Disease

Abstract: Background: Xuefu Zhuyu decoration (XFZYD), as a traditional Chinese compound recipe, has been used to treat atherosclerosis cardiovascular disease (ASCVD) for thousands of years in China, but its effective compounds and underlying treatment molecular mechanism remains promiscuous, which severely limits its clinical application.Methods: The effective components and their targets of XFZYD were predicted and screened based on the Traditional Chinese Medicine System Pharmacology (TCMSP) database. The candidate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Therefore, additional research studies are required in the future. The systemic pharmacology of XFZYD in the prevention of atherosclerotic cardiovascular disease (ASCVD) has shown that the mechanism of XFZYD is mainly reflected in the protection of vascular endothelium, prevention of oxidative stress, and inhibition of inflammation; the effective component quercetin was also shown to protect injured endothelial cells and reduce the endothelial inflammatory response (ICAM-1, VCAM-1, and TNF- α ) induced by LPS in vitro [ 47 ]. XFZYD has been shown to protect from ischemic necrosis, induce the migration of endothelial progenitor cells, and promote angiogenesis by improving the serum levels of NO [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, additional research studies are required in the future. The systemic pharmacology of XFZYD in the prevention of atherosclerotic cardiovascular disease (ASCVD) has shown that the mechanism of XFZYD is mainly reflected in the protection of vascular endothelium, prevention of oxidative stress, and inhibition of inflammation; the effective component quercetin was also shown to protect injured endothelial cells and reduce the endothelial inflammatory response (ICAM-1, VCAM-1, and TNF- α ) induced by LPS in vitro [ 47 ]. XFZYD has been shown to protect from ischemic necrosis, induce the migration of endothelial progenitor cells, and promote angiogenesis by improving the serum levels of NO [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Candidate target genes were identified in the GEO database (GSE9128, GSE71226), including total RNA expression data from coronary heart disease in human. GEO2R was used to identify the differentially expressed genes (DEGs), p ≤ 0.05, and |log FC| > 1 were the screening limitations [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…To support and extend the findings of previous in vivo research on mice, we selected mouse embryonic fibroblasts NIH/3T3, which are commonly employed in the cell senescence and oxidative stress model [23,24], to evaluate the protective effect of FCOPs on oxidative stress-induced damaged cells and its possible biological mechanism. Considering that the role of antioxidants may vary in different species and different tissues, we once more selected HUVECs, which are frequently utilized in the model of CVDs, since endothelial dysfunction caused by various factors, including oxidative stress, is the initiating factor of CVDs [25,26]. Given that CVDs are the most fatal chronic non-communicable illness, research into the protective role of FCOPs against oxidatively damaged HUVECs is crucial.…”
Section: Introductionmentioning
confidence: 99%